Social Identity Mapping in Addiction Recovery (SIM-AR): extension and application of a visual method. (2nd November 2019) - Beckwith, Melinda; Best, David; Savic, Michael; Haslam, Catherine; Bathish, Ramez; Dingle, Genevieve; Mackenzie, Jock; Staiger, Petra K.; Lubman, Dan I.
Abstract: Background: The Social Identity approach offers a unifying framework for understanding recovery from addiction as a process of identity change, associated with change in social network composition. This paper introduces Social Identity Mapping in Addiction Recovery (SIM-AR) — a visual method for capturing social group memberships, extended to integrate the substance use 'status' of group members as an indicator of group substance use norms. The aim here is to test theory-derived predictions focused on the relationship between changes in social identity and network composition reflected in groups' substance use norms in early recovery. Method: 155 therapeutic community (TC) residents in Victoria, Australia, completed the SIM-AR plus measures of substance-using and recovery identities and substance use shortly after admission, and 65% ( N = 101) again 6 months later. Results: As predicted, substance use severity at follow up was associated with changes in both social identity and network composition. Furthermore, reduced strength of substance-using identity was associated with a decrease in the proportion of groups with heavy substance use norms, while increased strength of 'recovery' identity was associated with an increased proportion of non-using groups. Conclusion: SIM-AR proved useful in testing predictions about social identity and network changes in a residential treatment context. It captured key social identity constructs in recovery using a visual technique with value to both research and applied contexts. Findings highlight the clinical importance of assessing a person's group-based relationships in treatment and early recovery, especially the influence of social group norms in relation to substance use.